Caregivers' experiences on preterm infants' management in a tertiary care facility in Ghana: a qualitative exploratory study - Mary Boadu; Senoo-Dogbey Vivian Efua; Ohene Lilian Akorfa; Armah Deborah; Irene Owusu Darkwa (BMC, 2024)
Background Preterm birth is a process that fundamentally alters parental or caregiver roles, particularly in the early weeks of childbirth. Caregiver experiences can be distressing due to struggles with an unfamiliar and potentially threatening environment of the Neonatal Intensive Care Unit (NICU). These experiences can affect the development of parenting or caregiving roles to a greater extent. Supporting caregivers of preterm infants through education and information sharing can significantly improve neonatal outcomes. This study sought to explore the experiences of caregivers with hospitalized preterm infants regarding the education and information they received from healthcare workers on the care of preterm infants. Method An exploratory descriptive qualitative study that explored caregivers' experiences with the management of preterm infants hospitalized at the Level III Neonatal Intensive Care Unit (NICU) of a tertiary level facility with an annual delivery of almost 7500 and a bed capacity of 26. The study utilized a deductive approach and a purposive sampling technique to recruit 16 caregivers who participated in an in-depth interview using a piloted semi-structured interview guide. The interviews were audio-recorded, transcribed, and analyzed using thematic analysis. Findings The study identified three major themes, which were (1) preterm infant feeding and keeping infants warm, (2) routine procedures and activities at the NICU, and (3) preparation towards homecare after discharge. Seven (7) sub-themes were generated. Caregivers were satisfied with the education and information they received on infant feeding and keeping the infant ward. They also had adequate education that prepared them for home care of the preterm infant. Caregivers did not receive timely information and education on the health status of their infants and the care processes of the NICU. They felt they were left out as they were not involved in decision-making. Regarding the care of the preterm infant. The inadequate flow of information and use of medical terminologies were a great source of worry and frustration for participants. The study showed that although the NICU staff were willing to offer health education to caregivers, information giving and education were not structured and hence did not address all the needs of the caregivers. Conclusion Healthcare providers caring for preterm infants include caregiver education in their routine NICU activities and procedures. These processes start from the period of admission till discharge. Their education sessions primarily focus on breastfeeding, keeping the infant warm and adequate preparation of caregivers for preterm infant home care. This notwithstanding there are gaps in caregiver education and information on routine procedures in the NICU as well as information on the health needs of the infant. Participants are not fully involved in the decision-making processes and the use of medical terminologies compound caregivers' frustrations and anxieties. It is important to develop structured educational programs tailored to address the information needs faced by caregivers to ensure optimal health outcomes for their preterm infants.